Markets for Local Flexibility in Distribution Networks - Julia Radecke; Joseph Hefele; Lion Hirth (ZBW – Leibniz Information Centre for Economics, 2019)
The three D's of the energy transformation – decarbonization, decentralization and digitalization – provide both chal-lenges and opportunities for distribution grids. Small-scale generation, batteries, electric heating, and e-mobility may put grids under considerable strain. However, if operated smartly, they also represent a deep pool of flexibility that can help grid operators relieve congestion and defer investment. One way of incentivizing such resources is to implement local markets for flexibility. In Europe, at least two dozen research pilots, stakeholder initiatives, and business cases have proposed specific designs for such markets. This paper provides an overview and analysis of these proposals. With many proposals being poorly documented, we largely rely on interviews for details on market design. We find that only one third of proposals allow free price formation, hence, despite their names, most are not what we consider a market. None of the proposals aims to replace existing congestion management mechanisms; rather they are meant as complementary tools. Usually markets employ dispatch payments; only few remunerate the reservation of flexibility availability. Though most proposals acknowledge market power and strategic interaction with other electricity markets (“inc-dec gaming”), few have developed concrete measures to address these problems. As they are in an early stage of development, market designs may still evolve.
Keywords: 330